Assessing Redox Properties of Natural Organic Matters with regard to Electron Exchange Capacity and Redox-Active Functional Groups. (14th April 2020) - Xu, Zhiyuan; Yang, Zhen; Wang, Hongping; Jiang, Jie
Abstract : Redox processes in groundwater play an important role in bioavailability, toxicity, and mobility of redox-active elements and contaminants. A recent study has demonstrated that low-molecular-weight fraction (LMWF) of humic substances with great number of redox-active functional groups (RAFGs) exhibits great reducing capacity. However, whether LMWF of natural organic matter (NOM) exhibits high redox capacity still remains unclear. Therefore, this study extracted Pahokee peat NOM (PPNOM) and Leonardite NOM (LNOM) from soils, and then LMWFs in these NOMs were collected using a dialysis method. Electron exchange capacities (EEC) and RAFGs of LMWF NOMs at different E h were analyzed using a novel electrochemical method and a three-dimensional excitation emission fluorescence (3DEEM) spectroscopy. We found that the reducing capacity in LMWF PPNOM was approximately 5-6 times higher than the bulk NOM, while only 7.8% LMWF PPNOM was accounted for in the bulk NOM. An increasing in EEC (EAC + EDC, where EAC is the electron accepting capacity and EDC is the electron donating capacity) of LMWF PPNOM and LNOM with E h reduced from −0.49 V to −0.69 V. Additionally, an obvious increase in fluorescent intensities of quinone-like fluorophores before and after being reduced LMWF LNOM is responsible for high EAC of LMWF LNOM. These findings provide a better understanding of relationship between RAFGs E h in LMWF of NOM, further helping in predicting and protection of groundwater environment and fate of transformation and transport for redox-active contaminants in groundwater.